HOW TO TEACH NEW METHODS EFFECTIVELY IN PRIMARY SCHOOLS - Rabbimova , Tulganoy Soyibovna; Fayzullayeva, Sitora Ziyodulla qizi; Burkhanova, Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
The article aims using new methods effectively in primary schools. To learn critical thinking of pupil making integratsion way to study methods and theme during the lesson. Students should learn tasks together teacher could create interrelated atmosphere among students.